Effect of Instrumental Music Therapy on Preoperative Anxiety Levels in Patients at Imanuel Hospital Bandar Lampung - Novian, Andreas Andri; Anita, Fitri; Yuliana, Dewi (Journal of Community Health Provision, 2024)
Anxiety is an uncomfortable feeling of powerlessness caused by unpleasant new experiences, resulting in tension, agtation, and loss of control due to subjective judgment. Anxiety often occurs in patients undergoing surgical procedures. The prevalence of anxiety in Indonesia in preoperative patients ranges from 45% to 75%. This piroves that the majority of paitents undergoing surgery expierience anxiety. One way to alleviate anxiety is through relaxation distraction techniques, such as instrumental usic therapy. The effects of instrumental music therapy include reducing stress and anxiety, as well as improving concentration. The statistical test results obtained a significance value oif 0.00 < p 0.05, indicating a significiant difference in the level of preoperative patient anxiety before and after being given instrumental music therapy intervention. Thus, it can be concluded that instrumental music therapy affects the level of preoperative patient anxiety at Imanuel Hospital Bandar Lampung. Suggestions for Imanuel Hospital are to implement instrumental music therapy as one of the nursing interventions to reduce anxiety in preoperative patients. With the provision of instrumental music therapy, it is hoped that patients undergoing surgery will feel calmer, allowing the surgical procedure to proceed simoothly and effectively.